2020
DOI: 10.2118/204226-pa
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study and Numerical Modeling of Boron Transport in Reservoir and Its Influence on Seawater-Breakthrough Calculation

Abstract: Summary Seawater injection is widely used to maintain offshore-oil-reservoir pressure and improve oil recovery. However, injecting seawater into reservoirs can cause many issues, such as reservoir souring and scaling, which are strongly related to the seawater-breakthrough percentage. Accurately calculating the seawater-breakthrough percentage is important for estimating the severity of those problems and further developing effective strategies to mitigate those issues. The validation of using n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…The comparison of the interfacial formation energy of the simulation systems with the experimental results of interfacial tension for different SDBS concentrations is shown in Figure . It can be found that in the process of describing the impact of SDBS concentration on the stability of the crude oil–water interface, the results of molecular dynamics simulation are basically consistent with the experimental results of interface tension, which further confirmed the reliability of the simulation calculation and experimental results in this paper. , …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The comparison of the interfacial formation energy of the simulation systems with the experimental results of interfacial tension for different SDBS concentrations is shown in Figure . It can be found that in the process of describing the impact of SDBS concentration on the stability of the crude oil–water interface, the results of molecular dynamics simulation are basically consistent with the experimental results of interface tension, which further confirmed the reliability of the simulation calculation and experimental results in this paper. , …”
Section: Resultssupporting
confidence: 84%
“…It can be found that in the process of describing the impact of SDBS concentration on the stability of the crude oil−water interface, the results of molecular dynamics simulation are basically consistent with the experimental results of interface tension, which further confirmed the reliability of the simulation calculation and experimental results in this paper. 53,54 5. CONCLUSIONS In this paper, to break through the limitations of model simplification and single-factor simulation in previous molecular dynamics studies, different oil−water interface system models were constructed according to the actual component composition of crude oil and water to investigate the impact of the concentration of surfactant SDBS on the stability of the crude oil−mineral water interface by molecular dynamics simulation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, new EOR technologies have been continuously developed. The primary and secondary recovery technologies provide recovery rates of 20–40%, whereas tertiary recovery technologies can afford recovery rates of 30–60%, greatly improving the oil recovery capacity. , EOR technology has evolved from the steam-assisted gravity drainage technology pioneered by Roger Butler to today’s chemically enhanced oil recovery technology, where displacement efficiency is continuously improved and chemical components such as alkalis, surfactants, and polymers are continuously injected in the rock formation. ,, However, there is a consensus that these chemical components will change the interface structure and behavior through the formation of adsorption layers, thus making the field of interface studies in the petroleum industry complex and diverse. , …”
Section: Introductionmentioning
confidence: 99%